2017
DOI: 10.1103/physrevlett.118.140402
|View full text |Cite
|
Sign up to set email alerts
|

Random Number Generation with Cosmic Photons

Abstract: Random numbers are indispensable for a variety of applications ranging from testing physics foundation to information encryption. In particular, nonlocality tests provide a strong evidence to our current understanding of nature -quantum mechanics. All the random number generators (RNG) used for the existing tests are constructed locally, making the test results vulnerable to the freedom-of-choice loophole. We report an experimental realization of RNGs based on the arrival time of cosmic photons. The measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Even if nature does not exploit the measurementindependence loophole, addressing the various assumptions experimentally has significant practical relevance for numerous entanglement-based technologies. These include device-independent quantum key distribution [47][48][49] along with random-number generation and randomness expansion [50][51][52][53][54][55][56][57][58]. In particular, a malicious adversary with knowledge of an opponent's devices could conceivably undermine a variety of quantum information schemes by exploiting the measurement-independence loophole [29,36,[59][60][61][62][63][64].…”
Section: Arxiv:180901307v2 [Quant-ph] 24 Jan 2019mentioning
confidence: 99%
“…Even if nature does not exploit the measurementindependence loophole, addressing the various assumptions experimentally has significant practical relevance for numerous entanglement-based technologies. These include device-independent quantum key distribution [47][48][49] along with random-number generation and randomness expansion [50][51][52][53][54][55][56][57][58]. In particular, a malicious adversary with knowledge of an opponent's devices could conceivably undermine a variety of quantum information schemes by exploiting the measurement-independence loophole [29,36,[59][60][61][62][63][64].…”
Section: Arxiv:180901307v2 [Quant-ph] 24 Jan 2019mentioning
confidence: 99%
“…It was also shown that the randomness loophole can be progressively addressed with cosmic RNGs [20][21][22], which take advantage of randomness at the remote celestial object to set the time constraint of local hidden variable mechanisms deep into the cosmic history. These works pave the way to construct a practical self-testing QRNG.…”
mentioning
confidence: 99%
“…RNGs including cosmic RNGs will be exploited to address the no-signaling issue in the input randomness [20][21][22]. For the current experiment, the settings are preset manually with parameters given by the Eberhard's optimization procedure as described above.…”
mentioning
confidence: 99%
“…The MDI method can tolerate arbitrarily low detection efficiencies for demonstration of EPR-steering [45], however, it would in turn reduce the randomness certification rate. In addition, the randomness generation protocol in our experiment requires initial randomness (random choice of measurement settings in each experimental trial), which could be strengthened, e.g., by pseudorandomness based on the arrival time of cosmic photons [46]. It is also of experimental interest to employ the randomness extraction process [49,50] We discuss how to construct a quantum-refereed steering witness (QRS) from a steering inequality.…”
Section: 106±0023mentioning
confidence: 99%